Pengaruh Gaya Kepemimpinan terhadap Kinerja Pegawai di Kantor Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Malang - Ahmad Zakky Mubarok; Eva Hany Fanida; Meirinawati Niswah; Fitrotun Niswah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to test and analyze the effect of leadership style on employee performance at the Secretariat Office of the Regional Representative Council (DPRD) of Malang Regency. This research uses an associative quantitative approach with a sample of 45 respondents drawn from a population of 83 employees. Data was collected through observation and closed questionnaires using a Likert scale, which was then analyzed using simple linear regression. The partial test (t-test) results showed a significance value of 0.018 (